Trama ecossistêmica turística da região das Cataratas do Iguaçu e sinalizadores rizomáticos de responsabilidade ecossistêmica - Sandi, Simone Maria (My University, 2024)
This dissertation has as general objective to present the characteristics of the tourism ecosystemic weave of the Iguassu Falls Region and the rhizomatic signs of ecosystemic responsibility. The specific objectives are: to discuss the concept of the ecosystemic turism and present its characteristics, related to the Iguaçu National Park; to present rhizomatic signs of the ecosystem involved in the research; carry out 'com-versations' with managers of the Iguaçu National Park and with tourists, on the characteristics of the ecosystem and the possibility of raising awareness of ecosystemic responsibility. The research questions are: What are the characteristics of the tourism ecosystemic weave of the Iguaçu Falls region and the rhizomatic signs of the ecosystemic responsibility? The theoretical framework involves: Tourism, with Beni and Moesch (2017), Barretto (2004), Moesch (2004), Baptista (2019; 2020a); Ecosystemic Responsibility, by Lovelock (1991, 2001, 2010), Capra (1997), Crema (1989), Baptista (2016); Rhizomes, covering the flying rivers and the Cataratas region, by Baptista (2017); Nobre (2014; 2015); Moss and Moss (2014). The methodological strategy is the Cartography of Knowledge, with a qualitative, pluri-methodological and procedural orientation, composed of the following trails: Intertwining-Nodes of Research Weave, Personal Knowledge or Subjective Dimension; Theoretical-Conceptual-Bibliographical Weave, Production Plant or Doings Weave; Research Intuitive Dimension. The Tourism-Weave and Ecosystemic Responsibility propositions, respectively, have proven adequate to address the phenomenon), because they allow the consideration of complexity and the ethical dimension. Tourism related to Iguaçu Falls is characterized by the search for contact with nature, a natural landscape rich in biodiversity, including differentiated fauna and flora. The rhizomatic logic, of complexity and dissipation of factors, is also observed, in the consideration of intertwined phenomena: flying rivers, hunting and illegal fishing in the Iguassu National Park. These phenomena demonstrate the interdependence in the performance of the ecosystem, with a direct relationship with each other, calling for an approach to tourism in its complexity. Signs of the importance of ecosystemic responsibility were identified, considering that there is a lot to be done, but there is also a certain level of awareness expansion, which can contribute to the coexistence between beings of all species and the appreciation of tourism in the region, in the sense of a logic guided by the ecosystemic responsibility. [resumo fornecido pelo autor]
Essa dissertação tem como objetivo geral apresentar as características da trama ecossistêmica turística da Região das Cataratas do Iguaçu e sinalizadores rizomáticos de responsabilidade ecossistêmica. São objetivos específicos: discutir o conceito de ecossistema turístico e apresentar suas características, relacionadas ao Parque Nacional do Iguaçu; apresentar sinalizadores rizomáticos do ecossistema envolvido na pesquisa; realizar 'com-versações' com turistas, colaboradores e gestores do Parque Nacional do Iguaçu, sobre as características do ecossistema e possibilidade de sensibilização para a responsabilidade ecossistêmica. Trabalha-se com a questão de pesquisa: Quais são as características da trama ecossistêmica turística da região das Cataratas do Iguaçu e sinalizadores rizomáticos de responsabilidade ecossistêmica? O referencial teórico envolve: Turismo, com Beni e Moesch (2017), Barretto (2004), Moesch (2004), Baptista (2019; 2020a); Responsabilidade Ecossistêmica, por Lovelock (1991, 2001, 2010), Capra (1997), Crema (1989), Baptista (2016); Rizomas, abrangendo os rios voadores e a região das Cataratas, por Baptista (2017); Nobre (2014; 2015); Moss e Moss (2014). A estratégia metodológica é a Cartografia de Saberes, de orientação qualitativa, plurimetodológica e processual, composta pelas trilhas: Trama dos Entrelaços-Nós da Pesquisa, Saberes pessoais ou Dimensão Subjetiva; Trama Teórico-Conceitual-Bibliográfica, Usina de Produção ou Trama dos Fazeres; Dimensão Intuitiva da Pesquisa. As proposições Turismo-Trama e Responsabilidade Ecossistêmica, respectivamente, têm se mostrado adequadas à abordagem do fenômeno, porque possibilitam a consideração da complexidade e da dimensão ética. O turismo relacionado às Cataratas do Iguaçu caracteriza-se pela busca do contato com a natureza, da paisagem natural rica em biodiversidades, incluindo fauna e flora diferenciadas. A lógica rizomática, de complexidade e dissipação de fatores, também é observada, na consideração de fenômenos que se entrelaçam: rios voadores, caça e pesca ilegal no Parque Nacional do Iguaçu. Esses fenômenos, demonstram a interdependência na atuação do ecossistema, com relação direta entre si, convocando à abordagem do turismo em sua complexidade. Foram identificados sinalizadores da importância da responsabilidade ecossistêmica, considerando que há muito a ser feito, mas também já existe certo nível ampliação da consciência, que pode contribuir para a convivência entre os seres de todas as espécies e a valorização do turismo na região, no sentido de uma lógica pautada pela responsabilidade ecossistêmica. [resumo fornecido pelo autor]
Keywords: Turismo - Iguaçu, Cataratas do (Brasil e Argentina); Ecoturismo; Tourism - Iguassu Falls (Brazil and Argentina); Ecotourism